Roles of Rac1 and Rac3 GTPases during the development of cortical and hippocampal GABAergic interneurons - de Curtis, Ivan (Frontiers in Cellular Neuroscience, 2014)
Rac GTPases are regulators of the cytoskeleton that play an important role in several aspects of neuronal and brain development. Two distinct Rac GTPases are expressed in the developing nervous system, the widely expressed Rac1 and the neural-specific Rac3 proteins. Recent experimental evidence supports a central role of these two Rac proteins in the development of inhibitory GABAergic interneurons, important modulatory elements of the brain circuitry. The combined inactivation of the genes for the two Rac proteins has profound effects on distinct aspects of interneuron development, and has highlighted a synergistic contribution of the two proteins to the postmitotic maturation of specific populations of cortical and hippocampal interneurons. Rac function is modulated by different types of regulators, and can influence the activity of specific effectors. Some of these proteins have been associated to the development and maturation of interneurons. Cortical interneuron dysfunction is implicated in several neurological and psychiatric diseases characterized by cognitive impairment. Therefore the description of the cellular processes regulated by the Rac GTPases, and the identification of the molecular networks underlying these processes during interneuron development is relevant to the understanding of the role of GABAergic interneurons in cognitive functions.